Strategies of the Party Selectorate: The Two-Level Game in District Selections in Germany’s Mixed Member Electoral System - Reiser, Marion (Frontiers in Political Science, 2022)
The article investigates how the opportunity structure and contextual factors influence the selectorates’ strategies in the process of candidate selection. The article argues that these strategies are an under-researched but important explanatory and dynamic link between the parties’ goals and context factors of candidate selection on the one side and the adopted selection criteria and the outcome of candidate selection on the other side. Based on a mixed-methods design, the study scrutinizes the selectorates’ strategies at district selections in Germany’s mixed-member electoral system. The analysis reveals that the local selectorates adopt the traditional inward oriented selection criteria to find the best candidate for the local party branch if the district seat is safe for the party. If, however, the seat is not safe, the selectorates prioritize the electoral goal over the local party organizational goal and strategically adapt the selection criteria to the opportunity structure. By considering both local inter-party competition and regional intra-party competition, they either take up a local voters’ perspective or anticipate the selection criteria of the state party lists in order to increase the chances for a seat in parliament. Thus, due to the mixed-member electoral system, the prevalence of dual candidacies, and decentralized candidate selection methods, intra-party selection in German districts is a two-level game.